Compact automotive thermoelectric generator with embedded heat pipes for thermal control - Pacheco, N. (2020)
Currently, the automotive industry faces challenges to implement solutions that provide reductions in energy consumption, pollutants and greenhouse-gas (GHG) emissions. Exhaust heat recovery employing Thermoelectric generators (TEGs) enables the direct conversion of heat into electric energy without moving parts and little to no maintenance. On-board electrical production is especially useful given the growing electrification trend of road vehicles. The present work assesses the performance of a novel temperature-controlled thermoelectric generator (TCTG) concept in a light duty vehicle and its impact on fuel economy and GHG emissions under realistic driving conditions. The novel exhaust heat exchanger (HE) concept consists of corrugated pipes embedded in a cast aluminium matrix along with variable conductance heat pipes (VCHPs) acting as spreaders of excess heat along the longitudinal direction. This concept seems to have a quite good potential for highly variable thermal load applications, as it is able to avoid overheating by spreading heat instead of wasting it through by-pass systems. Furthermore, when compared to previous concepts by the group, it does not need gravity assistance and has a form factor similar to conventional generators. It also appears to be capable of delivering a breakthrough electric output for TEG systems in such light vehicles, with as much as 572 W and 1538 W of average and maximum electric powers during a driving cycle, respectively, and showing a quite promising reduction of 5.4% in fuel consumption and CO2 emissions.